Is technological pedagogical content knowledge of history teachers decreasing day by day? A study on history students and current teachers? - Seitkhanuly, Issayev Mukhtar; Abubakirovich, Daniyarov Talgat; Tasbolatovna, Turayeva Aigul; Ayazbaykyzy, Zhumadullaeva Aigul; Akimkhanuly, Apendiyev Timur (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of this study is to compare the level of technological pedagogical content knowledge (TPCK) of prospective history teachers (university students) and current history teachers. In this context, 67 history teachers aged between 24 and 36 who are actively teaching history and 80 students aged between 18 and 22 from the Department of History, Faculty of Humanities participated in the study. The TPCK scores of the participants were determined using the 21st Century Skills of Technological Pedagogical Content Knowledge scale for Turkish culture developed by Alpaslan, Ulubey, and Ata (2021). According to the findings obtained in our study, students’ TPCK total scores (p < .001) and its sub-dimensions: Pedagogical Knowledge (PK) (p < .001), Technological Knowledge (TK) (p < .001), Content Knowledge (CK) (p < .001), Interaction of Pedagogical and Content Knowledge (IPCK) (p < .001), Interaction of Technological and Pedagogical Knowledge (ITPK) (p < .001), Interaction of Content and Technological Knowledge (ICTK) (p < .001), and Interaction of Pedagogical, Technological, and Content Knowledge (IPTCK) (p < .001) scores were significantly higher than those of current history teachers. As a result, it has been determined that the history department curricula of universities have been developed and updated within the framework of technological pedagogical and content knowledge, but current history teachers should be more active in TPCK.